The Uncertainty in Assessing the Claim for Damages Involving Common Specific Injuries Sustained from the Road Accident - Romli, Fariza; Mohd Subari, Nor Khatiha Asmida (2022)
Injury from collision typically has a significant physical impact on the victim. When an accident occurs, especially when it involves motorcycle riders, one of the most frequently damaged body parts is the limb. As a result, claims for bodily injuries resulting from running down cases invariably include the femur, tibia, and many other limbs. Knowing that a lawyer lacks fundamental medical knowledge and relies solely on their experience makes the total of claims uncertain and unpredictable. However, this issue has been somewhat resolved with the introduction of the Revised Compendium of Personal Injury 2018, raising the concern of uncertainty in terms of calculating and assuming amounts based on injuries, particularly common injuries. This paper makes use of the descriptive research to go through the need for typical injury claim amounts to be certain as well as the reasons why they cannot be. The methodology used is based on library research with an analysis of the law and cases. This paper came to the conclusion that although the existence of the Revised Compendium of Personal Injury 2018 has a positive effect on the legal community, due to its precariousness and ambiguity, the amount of each victim's claim may vary despite the similarity of their injuries. The Compendium only specified the range, extensively and enormously, somehow the numbers are stiff based on the lawyers' judgement.